Pembuatan Virgin Coconut Oil (VCO) Dengan Cara Penambahan Ragi Tempe - Razelita; Marmaini, Marmaini; Arif Setiawan, Andi (Indobiosains, 2024)
Virgin Coconut Oil (VCO) is an innovative coconut oil that is processed without using heating or chemicals . The aim of this research is to analyze the quality of VCO by adding tempeh yeast and fermentation time to the VCO obtained. The research was carried out in March-May 2024 and quality testing was carried out at the Biology Laboratory, Faculty of Science and Technology, PGRI University, Palembang. The research method was a survey and experiment, the survey was carried out on community plantations in Kumbang Ilir Village, Kandis District, Ogan Ilir Regency. The experimental method was carried out with 16 treatments and 3 repetitions, then the data was analyzed using a Completely Randomized Design (CRD) with 2 factors, factor 1 was a variation of adding control tempe yeast starter (without yeast), 15 ml, 30 ml, 45 ml, and factor 2 was a variation fermentation time 6, 12, 18, 24 hours. The research results showed that the highest value for the amount of VCO was 104 ml in the T 4 S 3 treatment, the lowest value was in the T 1 S 0 = 15 ml treatment. The lowest VCO yield value was in the T 1 S 0 treatment = 7.5%, while the highest VCO yield value was in the T 4 S 3 treatment = 52%. The results of the organoleptic test assessed by the respondents stated that 100% of the VCO obtained was clear in color, in the taste test 80% of respondents assessed the taste as typical of coconut and 20% had no taste, and in the aroma test 64% assessed the aroma as typical of coconut, 18% assessed it as slightly rancid, and 18% rated rancid.